Pengembangan Sistem Pengelolaan Tiket Klub Sepak Bola berbasis Web (Studi Kasus: Klub Sepak Bola Arema Malang) - Edwin Dwi Andrian; Denny Sagita Rusdianto; Djoko Pramono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Arema FC is one of the major soccer teams known in Indonesia which is headquartered in Malang, East Java. Every Arema FC home match is held at the Gajayana stadium or the Kanjuruhan stadium. Problems with Arema FC in the implementation of home match ticket games such as the lengthy process of booking tickets that is not efficient in terms of time, the exchange of hard tickets which is difficult to reach because they can only be exchanged at the head office, the lack of ticket payment options, operational working hours for purchasing tickets less flexible, and to the distribution of ticket sales which is very helpful because it goes through several stages. This system is built on a web-based basis using progressive web application technology that can be run, such as native applications and payment gateways, namely midtrans in the process of selecting payment options to support the ticket booking process. Arema FC. System development uses the waterfall approach with several stages, namely the analysis of development needs at the architectural design stage, component design, database design, and interface design which is used as a reference for system implementation and then the testing stage. The test includes three unit test cases and one Integration test that is valid, thirty-one validation tests are valid, and 1 compatibility test is valid and can run on several browsers such as chrome, safari, Edge.